Correction: Interlayer exciton emission in a MoS2/VOPc inorganic/organic van der Waals heterostructure. Issue 5 (10th March 2022) - Kong, Yuhan; Obaidulla, Sk Md; Habib, Mohammad Rezwan; Wang, Zukun; Wang, Rong; Khan, Yahya; Zhu, Haiming; Xu, Mingsheng; Yang, Deren
Abstract : Correction for 'Interlayer exciton emission in a MoS2 /VOPc inorganic/organic van der Waals heterostructure' by Yuhan Kong et al., Mater. Horiz., 2022, DOI: ; 10.1039/d1mh01622a .